PENGARUH DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI PADA YAYASAN TARBIYATU WAD DA’WAH ALKAUTSAR BOGOR TAJUR HALANG - Alwie Ardhana Rifaldi; Bunga Astra Gracia (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of work discipline and organizational culture on employee performance at the Tarbiyatu Wad Da'wah Al-Kautsar Bogor Tajur Halang Foundation, both partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling and the sample obtained in this study was 50 respondents. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing. The results of this research are that Work Discipline (X1) has a significant influence on the Employee Performance variable (Y). This can be proven from the results of research carried out through the t test, the calculated t value was (6.959 > 2.012). This is also reinforced by the significance value < 0.05 or (0.000 < 0.05). Thus, H0 is rejected and H1 is accepted, this shows that there is a significant influence between work discipline and employee performance. Organizational Culture (X2) has a significant influence on the Employee Performance variable (Y). This can be proven from the results of research that has been carried out through the t test, where a calculated t value of (5.864 > 2.012) was obtained. This is also reinforced by a significance value < 0.05 or (0.000 < 0.05). Thus, H0 is rejected and H2 is accepted, this shows that there is a significant influence between organizational culture on employee performance. Work Discipline (X1) and Organizational Culture (X2) have a significant influence on the Employee Performance variable (Y). This can be proven from the results of the F test where the calculated F value is (32.818 > 2.800), this is also reinforced by the significance < 0.05 or (0.00 < 0.05). Thus, H0 is rejected and H3 is accepted, this shows that there is a significant simultaneous influence between work discipline and organizational culture on employee performance at the Tarbiyatu Wad Da'wah Al-kautsar Bogor Tajur Halang Foundation.